Non-malignant disease mortality in meat workers: a model for studying the role of zoonotic transmissible agents in non-malignant chronic diseases in humans. Issue 12 (29th June 2007) - Johnson, E S; Zhou, Y; Sall, M; El Faramawi, M; Shah, N; Christopher, A; Lewis, N
Abstract : Background: Current research efforts have mainly concentrated on evaluating the role of substances present in animal food in the aetiology of chronic diseases in humans, with relatively little attention given to evaluating the role of transmissible agents that are also present. Meat workers are exposed to a variety of transmissible agents present in food animals and their products. This study investigates mortality from non-malignant diseases in workers with these exposures. Methods: A cohort mortality study was conducted between 1949 and 1989, of 8520 meat workers in a union in Baltimore, Maryland, who worked in manufacturing plants where animals were killed or processed, and who had high exposures to transmissible agents. Mortality in meat workers was compared with that in a control group of 6081 workers in the same union, and also with the US general population. Risk was estimated by proportional mortality and standardised mortality ratios (SMRs) and relative SMR. Results: A clear excess of mortality from septicaemia, subarachnoid haemorrhage, chronic nephritis, acute and subacute endocarditis, functional diseases of the heart, and decreased risk of mortality from pre-cerebral, cerebral artery stenosis were observed in meat workers when compared to the control group or to the US general population. Conclusions: The authors hypothesise that zoonotic transmissible agents present in food animals and their products may be responsible for the occurrence of some cases of circulatory, neurological and other diseases in meat workers, and possibly in the general population exposed to these agents.